Woman Transition from Myth to Interpretive-Literature: A Case-Study of Kashf al-Mahjub - Ifayi, Seddigeh; Hadidi, Khalil; Dehgan, Ali (Journal of History Culture and Art Research, 2017)
Abstract Women have been represented unpleasantly in most of the Persian literary texts. The apparent form of the Torah narration on the event of descent and imitation of some Islamic interpretative texts and repetition of the same concepts and contents in Persian literary texts such as Kashf-ul-Mahjub and Molana (Mawlana) works have caused these pessimistic views on the woman are rooted in the monotheism religions teachings. These thoughts and false beliefs are not assigned only to Iran and Persian literature, but it is a compressive thought that its example can be found in other cultures. Some anthropologists believe in shaping of these false thoughts about women rooted in their physical weakness or their insignificant role in the family economy or the male historiography which these issues were effective in expansion of pessimistic views about women. Although women played an important role in myths period in shaping important events and the society economy, however, the base of pessimistic view about them dates back to these myths, the period that women had exalted social place which they lost their status. This article tries to respond following questions: What was the relationship between woman and man in myths period? Why did they lose their holiness suddenly? To what extent the mythical stories were effective in being guilty of woman in man primary sin? What was the effect of this issue in shaping the elements of the story of descent narrated by the mystical literature in old texts such as Kashf-ul-Mahjub and Molana works?